A systematic survey of bar-built estuaries along the California coast. (15th October 2019) - Clark, Ross; O'Connor, Kevin
Abstract: Of California's 577 coastal confluences, 278 of these are characterized as bar-built estuaries or coastal river mouth lagoons. Development during the 20th century has led to varying and often extreme levels of alteration to these estuarine systems. Changes to the natural timing and magnitude of riverine flows and modification of the mouth have affected the frequency and depth of marsh plain flooding, as well as the timing of breaching events. This project used standard assessment techniques to document and quantify the current environmental condition of 32 bar-built estuaries of various sizes, distributed throughout California. Estuary lagoon filling/flushing patterns (documented using pressure/temperature loggers) were found to fluctuate most in spring (due to bar closure with continued fluvial discharge) and late fall (due to high wave overtopping events). These spring and fall water level increases led to marsh plain flooding. Marshes were flooded for periods ranging from 9 to 65 days. Sites that supported long summer ponding periods increased hydraulic connectivity with side channels and back water environments and were characterized as having optimal habitat condition using the California Rapid Assessment Method. Bar-built estuaries with lower condition were found to have higher abundance of agriculture and impervious surface within their watersheds. The lowest condition sites had more than 65% impervious surface within the 2 km radius around the bar-built estuary. Also, bar-built estuary systems where bar management occurred (periodic or permanent) were found to have a lower habitat condition and support fewer native plant species. Summer salinity exceeded 25 within portions of thirteen of the 32 estuaries and all but three systems had water within portions of the main channel with salinity below 5. Our findings suggest that water elevations, dissolved oxygen concentrations, salinity and temperature vary widely within bar-built estuaries and thus, management decisions should account for this variability to ensure support for a diversity of endemic species. Graphical abstract: Image 1 Highlights: The CRAM Index score for BBE habitat condition ranged from 33 to 90. Highly managed BBEs support less variable hydrology and poorer habitat condition. Variable water chemistry within BBEs provides unique habitats for various species. Mouth management should be weighed with regards to the needs of a full range of species and services.